Perilaku Phubbing dengan Kecerdasan Emosional Remaja pada Remaja SMA - Titi Sulastri; Khansa Khairunnisa; Santun Setiawati; Eviana S Tambunan; Yupi Supartini; Ratna Ningsih (Poltekkes Kemenkes Jakarta III, 2023)
Background: The phenomenon of phubbing is often found where a person is too engrossed on his smartphone so they don't care about the other person they are interacting with. The impact of this phubbing behavior makes a person unable to control his emotions and has emotional feelings that change easily because he feels that he has been controlled by his smartphone. The purpose of this study was to determine the relationship between the characteristics of the respondents and phubbing behavior with the emotional intelligence of adolescents. Methods: This research is a quantitative study with a correlational analytic approach. The sampling method was carried out using a stratified random sampling technique. The population of this study was 781 students, sample are 108 students. The independent variable is individual characteristics and phubbing behavior, the dependent variable is emotional intelligence. Data collection using the Generic Scale of Phubbing (GSP) questionnaire and the Trait Emotional Intelligence Questionnaire Adolescent Short Form (TEIQue-ASF). Data Analysis are Chi-Square, Mann Whitney, and Spearman Correlation with a significance level of α = 0.05. Results: 53.7% of respondents had phubbing at a moderate level and 56.5% of respondents had moderate emotional intelligence. There is a significant relationship between phubbing behavior and adolescent emotional intelligence (p=0.004), but there is no significant relationship between gender and age with emotional intelligence (p>0.05). Conclusion: There is a relationship between phubbing behavior and emotional intelligence, but there is no relationship between the characteristics of the respondents and emotional intelligence. In order to maintain adolescent emotional intelligence, adolescents need to avoid phubbing behavior when interacting or communicating with friends